A Noção De Scientia Na Terceira E Quarta Parte Do Prólogo Da Ordinatio De João Duns Scotus - Vanin, Andrei Pedro [UNIFESP] (2017)
This work aims to analyze the notion of scientia – scientific knowledge – in the third and first question of the fourth part the Prologue of John Duns Scotus' Ordinatio. The question that guides the work is this: how should scientia be understood in this text of Duns Scotus? From this main objective, there will also be a need to clarify another problem present in the text, namely, whether theology is a scientia in the strict sense. The formulation of scientia in Duns Scotus is based on Aristotle's definition of episteme. However, analyzing the notion of scientia and its background assumptions some differences can be noticed, mostly expansions, in comparison to the Aristotelian notion of episteme. Thus, this work seeks to map the way in which scientia is constructed in the prologue of the Ordinatio, taking as a basis the scientificity of theology.